Idiom, Syntax, and Advanced Theory of Mind Abilities in Children With Autism Spectrum Disorders. - Whyte, Elisabeth M.; Nelson, Keith E.; Scherf, K. Suzanne (Journal of Speech, Language & Hearing Research, 2014)
Purpose: When researchers investigate figurative language abilities (including idioms) in children with autism spectrum disorder (ASD), syntax abilities may be more important than once considered. In addition, there are limitations to the overreliance on false-belief tasks to measure theory of mind (TOM) abilities. In the current study, the authors investigated idiom, syntax, and advanced TOM abilities in children with ASD compared to children with typical development (TD). Method: Twenty-six children with ASD, ages 5 to 12 years, were compared to individuals in each of 2 control groups of children with TD: 1 matched on chronological age and nonverbal IQ, and 1 matched on syntax age-equivalence and raw scores. Idiom comprehension, syntax, vocabulary, and 2 measures of advanced TOM abilities were examined. Results: Although children with ASD performed worse on idiom comprehension compared to the age-matched group with TD, they exhibited comparable idiom performance to the syntax-matched group with TD. Advanced TOM abilities were related to idiom comprehension for children with ASD, but not for children with TD, above the contributions of basic language abilities. Conclusion: Syntax abilities should be used as a matching variable when examining figurative or other late-developing language skills.